ANALISIS KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA (STUDI KASUS : PEDAGANG SAYUR) TERHADAP PENDAPATAN KELUARGA DI PASAR SEUMAYAM KECAMATAN DARUL MAKMUR KABUPATEN NAGAN RAYA - Raidayani Raidayani; jelliani jelliani (Universitas Teuku Umar, 2019)
This study aims to analyze the Comparative Income of Vegetable Traders and family income in the Seumayam village People's Market, Darul Makmur District, Nagan Raya Regency. Data collection techniques use observations, questionnaires, and interviews by compiling detailed questions in a list of questions to test and find out how much income and contribution of women horticultural traders in Seumayam Market. Data analysis methodusing quantitative descriptive. And data processing in this research. The result of the study is that the total average of the vegetable traders is received is Rp. 3,737,080, - per month while the total average cost incurred by traders is Rp. 2,551,200 per month thus the average income of horticultural traders was Rp.1,185,880. The magnitude of horticultural traders' revenue contribution is affected family income is 28.0%, where the income contribution of the vegetable trader can help increase the resilience / household needs of the merchant himself